Pengaruh Layanan Bimbingan Kelompok terhadap Keberanian Bertanya Siswa di Kelas XI SMK Swasta Karya Utama Dolok Masihul Tahun Ajaran 2021-2022 - Rahmat Syaibani; Rodia Afriza (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to find out the influence of group mentoring services on the courage of asking students. The data capture technique consists of a lift. This research was carried out at Dolok Masihul Primary Teaching Year 2021-2022, which has a total of 10 students. The design of the study was pre-test and post-test group design. To obtain the data, the researchers used a closed lift and a concentration scale instrument of 45 particles, but after testing it turned out there were 8 invalid lifts, so the lifts used in this study were only 37. This study shows that the courage of asking students before giving group guidance services to students in class XI SMK Private Primary Works Dolok Masihul is in the middle category, this can be seen based on the average score of courage ask students before being given service of 85.3 then courage to ask students in grade XI SmK Private Main Works Dolek Masihul was in the medium category.